Konversi Suara Ke Teks Menggunakan Google Voice Sebagai Alat Bantu Komunikasi Tunarungu - Ocsirendi, Ocsirendi; Wijaya, Sastra; Aditya, Decxa; Dwisaputra, Indra (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
The ability to hear is a gift given by God to humans. By hearing, a person will be able to speak and communicate, but some of them are born with hearing loss or are known as deaf. Deafness is a condition where the sufferer loses their hearing so that deaf people experience difficulty in communicating with the person they are talking to because of limited hearing. The deaf communicate using sign language when communicating with the person they are talking to. The problem is that not all deaf interlocutors can use sign language to communicate. Hearing limitations cause deaf people to experience difficulties in interacting in society and the world of education because it is difficult for them to adapt to their surrounding environment. So in this research a tool was created that can make it easier for deaf people to communicate with normal people via an LCD display. By utilizing Google Voice as a user voice recording feature connected to the Android application. As a result of the tool that has been created, users can send voice messages via the Google Voice feature in the Android application, the voice messages that have been sent are then converted into text displays on the LCD, and the text that has been sent will be saved in the application history feature.